Expression of Serum LMAN2 and Sestrin2 in Septic Shock Patients and Exploration of Their Prognostic Value - Chen Z; Chu Z; Jia L (Journal of Inflammation Research)
Zhen Chen,1 Zhenyu Chu,1 Limin Jia2 1Department of Emergency, The First Affiliated Hospital of Soochow University, Suzhou City, Jiangsu Province, 251200, People’s Republic of China; 2Department of Emergency, Suzhou Municipal Hospital, Suzhou City, Jiangsu Province, 251200, People’s Republic of ChinaCorrespondence: Limin Jia, Department of Emergency, Suzhou Municipal Hospital, 26 Daoqian Street, Gusu District, Suzhou City, Jiangsu Province, 215002, People’s Republic of China, Email Jialiminemer@21cn.comObjective: The expressions and prognostic value of serum Lectin Mannose-Binding 2 (LMAN2) and Sestrin2 were evaluated in septic shock patients, aiming to provide new biomarkers for early diagnosis and prognosis judgment of septic shock patients.Methods: This retrospective study included 110 patients with sepsis and 50 healthy control subjects. Patients were classified into the sepsis group (SE group, 63 cases) or septic shock group (SS group, 47 cases) based on the occurrence of septic shock. Acute Physiology and Chronic Health Status II (APACHE II) scores, sequential organ failure assessment (SOFA) scores, and serum LMAN2 and Sestrin2 levels were compared between groups. The factors affecting the poor prognosis were analyzed by multivariate logistic regression. The receiver operating characteristic (ROC) curve was established to analyze the predictive value of serum LMAN2, Sestrin2, APACHE II score and SOFA score for the prognosis.Results: The serum LMAN2 levels in the SS group and SE group were significantly increased compared with the CON group, but the serum Sestrin2 levels were decreased (P< 0.05). The serum LMAN2 levels in the poor prognosis group were significantly higher than those in the good prognosis group, while the Sestrin2 levels were significantly decreased (P< 0.05). Serum level of LMAN2, APACHE II scores and SOFA scores were independent risk factors, but Sestrin2 level was protective factor (P< 0.05). Meanwhile, the AUC of serum LMAN2 and Sestrin2 combined detection was 0.894, and the specificity and sensitivity were 93.33% and 84.38%, respectively, which had high predictive value for the prognosis of septic shock patients. The AUC of serum LMAN2 and Sestrin2 combined with APACHE II score and SOFA score was 0.960, the specificity was 93.75%, and the sensitivity was 86.67%. Compared with the detection alone, the AUC of combined detection was increased (Z =− 2.166, − 2.758, − 2.059, − 2.172, P< 0.05).Conclusion: The increase of serum LMAN2 levels and the decrease of Sestrin2 levels were closely related to the severity of septic shock. The combined detection had important predictive value for the prognosis of septic shock patients. This study may have the potential to improve the management and treatment of sepsis patients.Keywords: LMAN2, Sestrin2, sepsis, septic shock, prognosis